Bridging the information gap: How Munda Makeover is transforming agricultural learning in Zambia - Owuor, Antonate Akinyi; Kramer, Berber; Ceballos, Francisco; Sambo, Kingsley (International Food Policy Research Institute, 2025)
This project note presents midline findings regarding the effects of Munda Makeover (MMO), a farm makeover TV show designed to disseminate agricultural knowledge to Zambian farmers in an entertaining way. IFPRI and partners designed and implemented a cluster randomized trial across 160 villages involving two main interventions: village screenings of MMO episodes, combined with weekly SMS reminders to watch the show; and agricultural roadshows or input fairs. Results from a phone survey with 976 farmers show that community screenings and SMS reminders significantly increased viewership and knowledge around innovations promoted in the TV show. However, the uptake of agricultural inputs sold during the roadshows remains limited, largely due to liquidity constraints. These findings offer critical insights for optimizing the delivery of agricultural extension content through mass media and improving farmers’ access to agricultural inputs.